Effect of fermentation on the peptide content, phenolics and antioxidant activity of defatted wheat germ. (December 2017) - Liu, Fengru; Chen, Zhengxing; Shao, Juanjuan; Wang, Chunxian; Zhan, Chen
Abstract: This work investigated the changes of free phenolics and peptides and their synergistic interaction in total antioxidant properties of defatted wheat germ (DWG) by the fermentation of Bacillus subtilis . DWG hydrolysates were found to have a significantly higher (P < 0.05) total phenolic content (26.09 mg Gallic acid equivalent (GAE) g −1 extract, dry weight) than non-fermented DWG (10.55 mg GAE g −1 ). Fermentation resulted in an increase in free phenolics (from 15% to 95% of total phenolic content), while a decrease in bound phenolics throughout the process. Fermentation changed the mode of polyphenol-protein interaction and promoted the release of free phenols. Meanwhile, there was an increase in peptide content (4.31% to 29.68%) within 48 h and followed by a decrease. The effects of peptides on the antioxidant activity were more significant than that of phenolic compounds in the early fermentation stage, but it was opposite in the later stage of fermentation. The antioxidant activity (~80%) was a positive correlation (R 2 = 0.972 and R 2 = 0.937, respectively) to both of phenolic content and peptide content during the fermentation due to the synergistic effects. Bacillus subtilis fermentation is an alternative for the production of phenolic and peptide compounds and enhancing antioxidant activity of the defatted wheat germ.